Routledge handbook on the Kurds - Gunter, Michael M. (Routledge handbooks, 2019)
With an estimated population of over 30 million, the Kurds are the largest stateless nation in the world. They are becoming increasingly important within regional and international geopolitics, particularly since the 2003 invasion of Iraq, the Arab Spring and the war in Syria. This multidisciplinary Handbook provides a definitive overview of a range of themes within Kurdish studies. Topics covered include: Kurdish studies in the United States and Europe, early Kurdish history, Kurdish culture, literature and cinema, economic dimensions, religion, geography and travel, Kurdish women, the Kurdish situation in Turkey, Iraq, Syria and Iran, the Kurdish diaspora. With a wide range of contributions from many leading academic experts, this Handbook will be a vital resource for students and scholars of Kurdish studies and Middle Eastern studies.